Forgotten joint score associated with prosthesis weight in cementless total hip arthroplasty: a prospective clinical study - Zeng, Huiliang; Li, Ping; Feng, Wenjun; Jie, Ke; Chen, Jinlun; Zeng, Jianchun; Chen, Xicong; Zhou, Guanming; Zhang, Haitao; Zeng, Yirong (Frontiers in Surgery, 2024)
This prospective study aimed to investigate the influence of weight difference between implanted prosthesis and removed bone in cementless total hip arthroplasty (THA) on hip awareness and patient-reported outcomes.A total of 48 patients (56 hips) who underwent primary THA were prospectively enrolled. Implanted prosthesis and removed bone were weighed intraoperatively. Forgotten Joint Score (FJS) and Western Ontario and McMaster Universities (WOMAC) scores were obtained before and at 1 and 3 months after surgery. Patients were divided into groups A, B, and C according to the percentile of the weight difference.The mean weight difference of the implanted prosthesis and removed bone was 117.97±47.35 g. A negative correlation was found among the weight differences of the three groups and 1-and 3-month postoperative FJS (correlation coefficients, -0.331 and -0.734, respectively). A positive correlation was found among the weight difference of the three groups and 3-month postoperative WOMAC (correlation coefficient, 0.403). A significant difference in 3-month postoperative FJS and WOMAC scores was found among the three groups. The mean 3-month postoperative FJS (79.00) of group C was significantly lower than that of group A (93.32) (P<0.05). The mean WOMAC score (15.83) of group A was significantly lower than that of group C (23.67) (P <0.05).The implanted prosthesis is larger than the removed bone in cementless THA. The weight difference is negatively correlated with hip function. The weight difference should be minimized to achieve optimal hip joint awareness. Level III, prospective controlled studies.